2017
DOI: 10.3390/ijerph14040376
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hypertension Accompanied by High Homocysteine and its Risk Factors in a Rural Population: A Cross-Sectional Study from Northeast China

Abstract: Previous studies found that hypertension and high homocysteine (HHcy) exhibited a synergistic effect on the risk of cardiovascular diseases. This study aimed to investigate the prevalence of hypertension accompanied by HHcy and its risk factors in the rural areas of northeast China. This study was conducted using a stratified cluster random sampling method, and included 6529 subjects with complete data. Demographic characteristics were obtained from a questionnaire. Blood pressure and anthropometric indices we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Actually, only a small number of hypertensive patients have an elevated blood pressure alone, with the majority exhibiting additional cardiovascular risk factors, such as obesity [ 3 ], dyslipidemia [ 4 ], and hyperuricemia [ 5 ]. It was worth noting that about 75% of hypertensive patients exhibit high homocysteine (Hcy) in China [ 6 ] and several studies have revealed that hyperhomocysteinemia interacts with hypertension in significantly increasing the risk of cardiovascular events (CVE) [ 7 ]. Elevated Hcy diminishes the vasodilation of nitric oxide, increases oxidative stress, stimulates the proliferation of vascular smooth muscle cells, lead to vascular constriction, and alters the elastic properties of the vascular wall [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, only a small number of hypertensive patients have an elevated blood pressure alone, with the majority exhibiting additional cardiovascular risk factors, such as obesity [ 3 ], dyslipidemia [ 4 ], and hyperuricemia [ 5 ]. It was worth noting that about 75% of hypertensive patients exhibit high homocysteine (Hcy) in China [ 6 ] and several studies have revealed that hyperhomocysteinemia interacts with hypertension in significantly increasing the risk of cardiovascular events (CVE) [ 7 ]. Elevated Hcy diminishes the vasodilation of nitric oxide, increases oxidative stress, stimulates the proliferation of vascular smooth muscle cells, lead to vascular constriction, and alters the elastic properties of the vascular wall [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these mechanisms, several factors could influence the development of BC. As a previous study has suggested, different dietary patterns may contribute to the observed differences in Hcy, which could upset the balance between the production and degradation of Hcy, resulting in HHcy [27]. These results suggest that the dietary pattern of studied population is rich in fat, food processing and freezing, which could contribute to weight gain in women with BC.…”
Section: Discussionmentioning
confidence: 49%
“…Nevertheless, HHcy is considered a risk factor in BC patients with increased body mass index (BMI; overweight, obesity). A variety of mechanisms for obesity and HHcy have been proposed that could contribute to the development of BC [27].…”
Section: Discussionmentioning
confidence: 99%
“…They completed one questionnaire for the collection of relevant information, such as medical history, family history and socioeconomic factors. The details of the study design have been reported in previous papers, which were all cross-sectional analyses [19][20][21]. To better evaluate the possible CV risk factors among rural residents, a follow-up study was conducted from 2015 to 2017.…”
Section: Participantsmentioning
confidence: 99%